. . . und . . . Fried . . . und . . .: The Poetry of Erich Fried and the Structure of Contemporaneity - Nora M. Alter (Studies in 20th & 21st Century Literature, 1997)
This essay looks at the poetry of Erich Fried in the context of tensions within contemporary cultural studies. Fried's contemporaneity is linked to his status on the margins of various cultures, media, and ideologies—thus making both his life and his works appear as exemplary paradigms for the postmodern condition, with its various theoretical celebrations of "exile," "border crossing," "transgression," "deterritorialization," and so forth. Yet, at the same time, seemingly in contrast with his labile identity is Fried's rigid Marxist political ideological core which surfaces in his political poetry. Focusing, in particular, on Fried's poems directed against the Vietnam War, this essay seeks to situate the tension beteen these two positions as a deep structure already in his work.
Keywords: Erich Fried; contemporary cultural studies; tension; context; contemporaneity; margins; culture; media; ideologies; postmodern condition; exile; & quot; border crossing& quot; & quot; transgression& quot; & quot; deterritorialization& quot; labile identity; identity; Marxist; political; ideological; political poetry; poetry; Vietnam War